The Effects of Different Drivers on the Induced Martian Magnetosphere Boundary: A Case Study of September 2017. Issue 2 (5th February 2021) - Lentz, C. L.; Baker, D. N.; Andersson, L.; Thaller, S.; Fowler, C. M.; Leonard, T. W.
Abstract: The Magnetic Pileup Boundary or Induced Magnetosphere Boundary (IMB) has been an enigma in Mars aeronomy. Previously dubbed the planetopause, magnetopause, ion‐composition boundary, and protonopause, identification of this unique plasma region has been marked by difficulty. In this case study, we used data from the Mars Atmosphere and Volatile EvolutioN (MAVEN) mission to identify IMB crossings and configurations during the month of September 2017, with a particular focus on the September 10, 2017 solar events. It was concluded that the Interplanetary Coronal Mass Ejection had no statistically significant impact on the IMB standoff locations. This study also investigated the effects of upstream dynamic pressure, thermal pressure from the magnetosheath, magnetic pressure from the magnetic pileup region (MPR), thermal pressure associated with the ionosphere, and Extreme Ultraviolet irradiance on the IMB during September 2017. We have found that during the 163 IMB crossings, magnetic pressure in the MPR and thermal pressure in the ionosphere had the largest influence on the IMB standoff distance. Plain Language Summary: The plasma environment of Mars is a dynamic and complex place. There are multiple layers and confines of plasma formed from the interaction of plasma from planetary origin and the plasma of the solar wind. One such complicated plasma boundary is the Induced Magnetosphere Boundary (IMB) which is one of many located in the solar wind/ionosphere interface region. The IMB is widely known to be affected by solar wind dynamic pressure and solar irradiance flux. However, there are other pressures that sway the position and shape of the IMB as well. September 2017 brought about an intense pressure event due to the solar eruptive activity. All aspects of the Martian plasma environment were affected. We therefore took this opportunity to examine how the IMB reacted to different plasma pressures brought about by the solar events. We also tried to determine which pressure(s) were most influential in determining the IMB's standoff distance. Key Points: The Interplanetary Coronal Mass Ejection during September 2017 had no statistically significant impact on the Induced Magnetosphere Boundary (IMB) standoff location The magnetic pressure of the magnetic pileup region and the thermal pressure of the ionosphere had the greatest influence on the IMB standoff distance during September 2017